Hydrocarbon Potential of the Late Permian and the Late Triassic Source Rocks from the Qamdo (Changdu) Basin, Eastern Tibet and Its Linkage with the Sea Level Change - Qi, Zhaolin; Li, Yalin; Wang, Chengshan (Frontiers in Earth Science, 2021)
The Qamdo Basin in eastern Tibet has significant petroleum potential and previous studies indicate that the basin contains thick potential source rocks of the Late Permian and the Late Triassic ages. In this paper, the petroleum potential of samples from measured the Upper Permian and Upper Triassic outcrop sections was evaluated on the basis of sedimentological, organic petrographic and geochemical analyses. Initial evaluations of total organic carbon (TOC) contents indicated that shale samples from the Upper Permian Tuoba Formation and the Upper Triassic Adula and Duogala Formations have major source rock potential, while carbonate rocks from the Upper Triassic Bolila Formation are comparatively lean in organic matter (OM). More detailed analyses of OM-rich shale samples from the Tuoba, Adula and Duogala Formations included Rock-eval, elemental analyses, gas chromatography and organic petrography. Maceral compositions and plots of atomic O/C versus H/C indicate that the organic matter present in the samples is primarily Type II with a mixed source. Analyses of acyclic isoprenoid biomarkers indicate the organic matter was deposited under reducing and sub- to anoxic conditions. Based on the high vitrinite reflectance (Ro>1.3%) and Rock-eval data, the samples are classified as highly to over-mature, suggesting that the Tuoba, Adula and Duogaila Formation shales may generate thermogenic gas. Source rock intervals in the three formations are interpreted to have been deposited in marginal-marine environment during transgressions and under a warm and moist climatic condition.